2014
DOI: 10.1186/1477-7819-12-121
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-regulated protein 78 and heparanase expression in oral squamous cell carcinoma: correlations and prognostic significance

Abstract: BackgroundThe aim of the present study was to investigate the expression of glucose-related protein 78 (GRP78) and heparanase (HPA) in oral squamous cell carcinoma (OSCC) and their relationship with clinicopathological parameters and potential implications for survival.MethodsA total of 46 patients with OSCC and 10 normal individuals were recruited for the study. GRP78 and HPA expression were determined in the lesion tissues using immunohistochemical analysis. The correlation between GRP78 and HPA was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…It is well documented that GRP78 protein is expressed normally in the cell membrane of many cell types as GRP78 might act as a signal transduction receptor in the plasma membrane via the PI3K-Akt axis [21]. In cancer cells, the expression of GRP78 protein is extended to include cytoplasm, which is consistent with previous studies [22,23]. The increase in the cytoplas-mic expression of GRP78 in cancer cells is part of UPR pathway required for processing of misfolded proteins in the lumen of the ER that are accumulated during cancer progression.…”
Section: Discussionsupporting
confidence: 88%
“…It is well documented that GRP78 protein is expressed normally in the cell membrane of many cell types as GRP78 might act as a signal transduction receptor in the plasma membrane via the PI3K-Akt axis [21]. In cancer cells, the expression of GRP78 protein is extended to include cytoplasm, which is consistent with previous studies [22,23]. The increase in the cytoplas-mic expression of GRP78 in cancer cells is part of UPR pathway required for processing of misfolded proteins in the lumen of the ER that are accumulated during cancer progression.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, we attempted to clear up that confusion with respect to laryngeal SCC. GRP78/BiP has been observed to be elevated in the majority of solid tumors, and its high expression has been found to correlate with shorter survival, high pathological grade, aggressive phenotype, and poor prognosis . However, the upregulation of GRP78/BiP in lung cancer has been reported to be indicative of better prognosis; moreover, positive expression of GRP78/BiP in patients with neuroblastoma was closely associated with longer survival times .…”
Section: Discussionmentioning
confidence: 99%
“…Extensive expression of GRP78/BiP is found in many cancer cell lines and human neoplasms, and its expression is known to be closely associated with drug resistance, metastasis, tumor growth, survival, and resistance to chemotherapy . Several researchers have described that the expression level of GRP78/BiP plays an essential role in survival and tumor aggressiveness in patients with cancer, including lung cancer, breast cancer, prostate cancer, gastric cancer, and hepatocellular carcinoma . Of the patients with head and neck cancer, studies focused on the patients with oral SCC and found a close relationship between the expression level of GRP78/BiP and indicators of tumor progression, such as metastasis, disease stage, and survival .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations